IMPACT OF AGE AS A SOCIO-DEMOGRAPHIC VARIABLE ON HEALTH INSURANCE PRODUCTS - Cătălin CÂMPEANU (Management & Marketing)
The private health insurance has taken off over the recent years, boosted by the pandemic of COVID 19, setting the pace for other similar products, over a market severely dominated by MTPL. However, there were numerous factors influencing this growth, starting with state policies, insurance companies’ management along with welfare and socio-demographic factors. This paper addresses some of the later by focusing on age and notoriety, aiming to determine the possible correlation between socio-demographic variables such as age and health insurance products. The data used were provided by a recent study, conducted by the Institute of Financial Studies, an organization specialized on nonbanking financial system, gathered through a questionnaire, focused on a relevant group, considering all the necessary indicators regarding age, financial situation, area of living, studies, etc.